Les aînés francophones de l’Ontario : un portrait de santé. - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

Language as an important determinant of poverty in the aging Francophone minority population in Canada - Bouchard, Louise; Sedigh, Golnaz; Batal, Malek; Imbeault, Pascal; Makvandi, Ewa; Sylva de la Vega, E. (The International Journal of Aging and Society, 2013)
Six cycles of the Canadian Community Health surveys (CCHS) from 2001 to 2009 were used to compare the income and health of the minority French-speaking aging population (over 65 years of age) to the majority English-speaking group in Canada, excluding Quebec. A sequential multivariate logistic regression analysis showed that men and women of the minority French-speaking population of this age group, living in Canada outside the province of Quebec, are more likely to be in the poorest income quintile than their English-speaking counterparts. This disparity remains significant even after controlling for residence (province and urban/rural), household makeup (living alone or not), immigration status, education, employment, health status, chronic diseases, and restrictions in activities. Independently of other key socio-demographic factors modulating health, our results also show that being in the poorest income quintile is associated with a poor self-perceived health, a finding that was more prevalent in the French-speaking aging population living in situation of minority.

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Comparison of dietary intake between Francophones and Anglophones in Canada: Data from CCHS2.2 - Batal, Malek; Makvandi, Ewa; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective To compare the dietary intake and food choices between Francophone Canadians in a state of linguistic minority (outside of Quebec) and the English-speaking majority. Methods We used the 2004 Canadian Community Health Survey (CCHS) cycle 2.2 (general health and 24-hour dietary recalls) to describe dietary intake of Francophone Canadians (excluding Quebec) and compare them to the English-speaking majority. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. The mean differences in daily nutrient and food intake were assessed by t and chi-square tests. Results Differences in total energy and daily food intakes by language groups were not observed in the sample; however, significant differences in weekly consumption were found in different age and sex categories: lower fruits and vegetables consumption, and vitamins and macronutrients intakes for older Francophone men and higher intakes of energy and saturated fat from “unhealthy” foods for Francophone men 19–30 years of age. Based on the Acceptable Macronutrients Distribution Range (AMDR), approximately 50% of the sample exceeded their acceptable energy intake from saturated fats, and 80% were below their required intake of linoleic fatty acid. Conclusion We confirmed that belonging to Francophone minorities in Canada affects food choices and nutritional well-being of this population. The most vulnerable groups identified by our study were Francophone men in the youngest (19-30) and older (50 and over) age categories. The extent to which the cultural setting influences the diet and, in turn, the health of the minority population needs further examination.